2015
DOI: 10.1086/683838
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Rationality and Welfare

Abstract: Abstract. There is ample evidence to show that choice behavior often deviates from the classical principle of maximization. This evidence raises at least two important questions: (i) how severe the deviation is and (ii) which method is the best for extracting relevant information from the choices of the individual for the purposes of welfare analysis. In this paper we address these two questions by proposing a set of foundational conditions on which to build a proper measure of the rationality of individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 43 publications
0
78
0
Order By: Relevance
“…In the latter paper, it is also shown that computing the money pump index for the most and least severe violations can be done in polynomial time. Furthermore, Apesteguia and Ballester (2015) introduce the minimal swaps index. Informally, the swaps index of a given preference ordering over the alternatives is calculated by counting how many better alternatives (according to the preference order) were not chosen over all choice situations.…”
Section: Goodness-of-fit Measuresmentioning
confidence: 99%
“…In the latter paper, it is also shown that computing the money pump index for the most and least severe violations can be done in polynomial time. Furthermore, Apesteguia and Ballester (2015) introduce the minimal swaps index. Informally, the swaps index of a given preference ordering over the alternatives is calculated by counting how many better alternatives (according to the preference order) were not chosen over all choice situations.…”
Section: Goodness-of-fit Measuresmentioning
confidence: 99%
“…Echenique, Lee, and Shum (2011) provided a new measure based on a money pump argument, and Dean and Martin (2015) provided a new measure based on the minimum cost of breaking all cycles or money pumps. Apesteguia and Ballester (2015) provided a measure based on welfare loss.…”
Section: The Afriat Efficiency Indexmentioning
confidence: 99%
“…The minimal game tree that may explain boundedly rational behavior following Xu and Zhou (2007) has two agents and two nodes. Kalai (2002), Ambrus and Rozen (2015), Apesteguia and Ballester (2014) and Manzini and Mariotti (2012) define yet further measures of irrationality.…”
Section: Theorem 1 Fix a Housing Problem C And A Hierarchical Exchangmentioning
confidence: 99%